Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial: research article - Koch, Elias A. T.; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.